Communities and Networks : Using Social Network Analysis to Rethink Urban and Community Studies - Giuffre, Katherine (Chichester : Polity Press, 2013)
In Communities and Networks , Katherine Giuffre takes the science of social network analysis and applies it to key issues of living in communities, especially in urban areas, exploring questions such as: How do communities shape our lives and identities? How do they foster either conformity or innovation? What holds communities together and what happens when they fragment or fall apart? How is community life changing in response to technological advances? Refreshingly accessible and built on fascinating case examples, this unique...
Chapter 1: What is network analysis and how can it be useful? Chapter 2: Wha is a community? Where does it come from? Chapter 3: What do communities do for us? Chapter 4: How do communities shape identity? Chapter 5: What happens when communities become fractured? Chapter 6: How do communities mobilize for collective action and social movements? Chapter 7: How do communities foster creativity and innovation? Chapter 8: How do new communities differ from traditional communities? Glossary of Network Terms References.
Includes index and references : p. 216-221.
Keywords: Bysociologi; Communities